Pengaruh Bauran Pemasaran Dan Analisis Optimalisasi Faktor Produksi Pada Industri Kecil Sari Kedelai NONY di Kabupaten Tulungagung - Program Arryanto Putra (Universitas Islam Kadiri, 2019)
NONY is one form of small business engaged in the agribusiness processing of agricultural products in the form of soy extract. But as time passes, more and more business actors engaged in the same field. This will undoubtedly threaten the existence of NONY company in producing soybean extract, sharing various strategies must be done so that this company can survive. Therefore it is necessary to analyze the optimization of production factors to determine what production factors need to be improved or reduced. Also important thing is from marketing side, NONY company need to do marketing mix analysis satisfyed consumer in order to maintain customer loyalty that make company can survive. This study uses multiple linear regression method to find analysis of factor optimization and marketing mix analysis to NONY soybean consumers. For analysis of production factor optimization using Cobb Douglas factor input analysis. Using 100 screening samples in order to obtain good results, followed by looking for the influence of marketing mix to consumers The result of this research shows that sugar production factor is very influential to NONY soybean production process and it is necessary to reduce the use of taste and worker to increase the optimization of production. Product and Promotion factor in marketing mix influences consumer's satisfaction and loyalty, where the consumer of NONY soybean extract comes in. in the medium category.